Minat Generasi Z Terhadap Belanja Online Tiktok Shop di Kabupaten Bener Meriah - Ramadan, Hendra (Indonesian Journal Publisher, 2024)
Advances in technology and access to information have significantly changed the dynamics of society, as evidenced by the rise of online shopping platforms, commonly referred to as e-commerce. One of the benefits of the digital era is the ease of shopping online. Through online shopping platforms and product images, we can sell and buy goods practically. The purpose of this study is to test and analyse the effect of generation Z's interest in online shopping at TikTok Shop and also to test and analyse generation Z's digital behaviour towards online shopping at TikTok Shop. The method used in this research is quantitative using a sample of 100 respondents selected through purposive sampling method in Redelong City, Bener Meriah Regency. Data were collected through questionnaires distributed via social media and analysed using multiple linear regression. The results showed that the variables of interest (X1) and digital behaviour (X2) had a positive and significant effect on generation Z online shopping in Bener Meriah Regency. Then the independent variables contribute simultaneously 53.1% to generation Z shopping at TikTok Shop (Y). While other factors contributed 46.9%, the rest was influenced by other variables. It can be concluded that the preference of generation Z who has an interest and also a behavioural attitude towards the TikTok shop platform to do this shopping is due to interactive, attractive multimedia content, consumer confidence, and the platform's ability to provide a shopping experience with good service.